(3efGbH GdEeGe eGdcs
(3ChdgG (B:s
(3GdMeO ddg GdPi LYd GdYde ddYdeGA fSHkG hCZfGge Hg hSei YGde GdeOjfI hETJgQ Ydeg HGdCeUGQ hGTJgQ ai SGFQ GdCbWGQ s
(3BNQgG (B:s
(3hef gOGfG dOjf bO SeG TQbkG hbOQkG GfJgi ef cJGH GdQhV GdaGFb ai GdehGYX hGdQbGFb s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B3s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdeLGejYs